The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1093/hropen/hoac039
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of menstrual cycles with or without intercourse in women with no known subfertility

Abstract: STUDY QUESTION Does sexual intercourse enhance the cycle fecundability in women without known subfertility? SUMMARY ANSWER Sexual intercourse (regardless of timing during the cycle) was associated with cycle characteristics suggesting higher fecundability, including longer luteal phase, less premenstrual spotting, and more than two days of cervical fluid with estrogen-stimulated qualities. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
2
2
0
Order By: Relevance
“…Our results build on prior work evaluating the menstrual cycle characteristics of women using period tracking apps. The median cycle length, 28.7 days in our study, is consistent with previous studies and period tracking app data 17,[20][21][22][23][24] .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results build on prior work evaluating the menstrual cycle characteristics of women using period tracking apps. The median cycle length, 28.7 days in our study, is consistent with previous studies and period tracking app data 17,[20][21][22][23][24] .…”
Section: Discussionsupporting
confidence: 92%
“…The copyright holder for this preprint this version posted October 21, 2022. ; https://doi.org/10.1101/2022.10.20.22280407 doi: medRxiv preprint using period tracking apps. The median cycle length, 28.7 days in our study, is consistent with previous studies and period tracking app data 17,[20][21][22][23][24] . Somatic symptoms were reported most frequently, with cramps being the most reported symptom.…”
Section: (Which Was Not Certified By Peer Review)supporting
confidence: 92%
“…The similar enrichment patterns when partitioning heritability for UL and that of sexual factors further elucidate potential overlapped etiology related to the immune system. A chronically active inflammatory immune system is suggested to be involved in UL formation [ 45 , 46 ], and sexual factors are linked to sex hormones [ 6 , 7 ] which have well-established impacts on immune responses [ 47 ]. Future work is warranted to fully uncover specific pathways that underlie the UL-AFS/NSP biological associations.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, sexual factors such as age at first sexual intercourse (AFS) and lifetime number of sexual partners (NSP) receive little empirical attention, even with a decrease in AFS and an increase in NSP being observed in many contemporary societies [3][4][5]. In addition to impacting ovulation and hormonal concentrations [6,7], sexual factors may expose participants to infectious agents in the uterus [8,9]. Therefore, low AFS or high NSP may correlate with alterations in sex hormones and/or an increased susceptibility to uterine infections, both of which have previously been hypothesized to play an etiologic role in UL pathogenesis [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…In a study that included 581 women who contributed 3324 cycles, the majority were <30 years of age (74.5%), non-Hispanic white (88.6%), and nulliparous (70.4%). The mean menses length was 6.2 days (SD = 1.5, range 3-15), and 11.6% of all participants experienced a >3-day difference between the longest and shortest menses length [42]. The study by Park et al reported an average duration of bleeding of 5.6 days; 95.2% reported bleeding between 2 and 7 days and 4.8% reported more than 8 days of bleeding [43].…”
Section: Bmi Rangementioning
confidence: 93%